El teatro y las representaciones escénicas en la vida cotidiana de los madrileños durante el siglo xvii - Gloria Franco Rubio (Mélanges de la Casa de Velázquez, 2025)
There is no doubt that theatre and theatrical performance were one of the most unique recreational, sociological and cultural phenomena of modern society. It was promoted and practised by almost all writers who prided themselves on being so, as well as by those who wished to be recognised under that name; it was praised by cultivated minds who read the theatre with real pleasure; it was supported by noble and ecclesiastical patronage; performances were produced in all kinds of settings, permanent and improvised, civil and religious and, after all, applauded by all kinds of spectators. Theatre was also recognised as one of the most popular pastimes of everyday festive life and, almost certainly, the favourite entertainment of the majority of the population. Its social relevance lies in its performance as one of the most powerful instruments for transmitting the dominant ideology, as an effective tool for political and religious propaganda, as a vector of opinion and also as an interesting laboratory for current affairs. It has always had a large number of followers, from all classes and social groups, but this has not prevented the emergence of a large group of detractors, whose dialectical confrontation due to the disparity of opinions has given rise to a social debate on its moral legitimacy, which has given rise to one of the most suggestive and long-lasting controversies.